2021
DOI: 10.2147/ijwh.s338910
|View full text |Cite
|
Sign up to set email alerts
|

Primary Lung Cancer After Treatment for Breast Cancer

Abstract: Breast cancer is the most common malignancy in women and the second most common cause of cancer-related death. Due to advances in the diagnosis and treatment technologies for breast cancer, patients with breast cancer are living longer than before, resulting in an increased risk of developing subsequent malignancies, among which lung cancer is the most common. This review presents the current evidence about the risk, influencing factors and prognostic factors of developing primary lung cancer after treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…The authors note that although the absolute risk is relatively low, the growing number of long-time survivors after breast cancer treatment highlights the need for advances in normal tissue sparing radiation techniques [ 47 , 48 ]. Encouragingly, some novel approaches recently described appear to achieve this end, based on dosimetric calculations [ 51 ].…”
Section: Sex and Age Modulate Secondary Cancers Attributable To Exter...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors note that although the absolute risk is relatively low, the growing number of long-time survivors after breast cancer treatment highlights the need for advances in normal tissue sparing radiation techniques [ 47 , 48 ]. Encouragingly, some novel approaches recently described appear to achieve this end, based on dosimetric calculations [ 51 ].…”
Section: Sex and Age Modulate Secondary Cancers Attributable To Exter...mentioning
confidence: 99%
“…TRT presents a challenge for risk modulation to healthy organs since healthy tissue sparing strategies which can be deployed with external radiation [ 51 ] are not relevant when the radioactive agent is administered systemically. Instead, TRT trials incorporate individual dosimetry to predict risk of toxicity as well as efficacy [ 98 , 109 , 110 , 111 ].…”
Section: Sex Hormonal Status and Targeted Radionuclide Therapy: A Cha...mentioning
confidence: 99%
“…In this case, the patient had a number of risk factors for developing second primary lung cancer, including older age at breast cancer diagnosis (>50 years old) and a strong family history of malignancy [ 10 ]. Although previous studies have suggested a higher incidence rate of second primary lung cancers among patients with ER, PR, and HER-2 negativity [ 10 - 12 ], our patient had triple positive breast cancer, suggesting a potential alternate pathway to the development of her lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer often appears in metachronous cancer in the form of a second primary cancer. There is evidence that the risk of primary lung cancer after treatment of breast cancer increases because smoking habits, age and the disease stage of breast cancer may affect the risk of secondary primary lung cancer in breast cancer patients[ 38 ]. Therefore, the regular follow-up of patients, including monitoring the lungs after 6 mo, should be carried out while breast cancer is treated.…”
Section: Discussionmentioning
confidence: 99%